Phytochemical Analysis And Potential Anticancer Activity Of Propolis Extract Derived From Malaysian Trigona Apicalis In Human Cervical Cells - Gapar, Nur Adilah Abdul (2018)
Propolis is a resinous substance of beehive which is made from various sources of a plant. It exists in yellow to dark brown in colour depending on its age and sources. Propolis is well known for its therapeutic properties. It possesses a wide range of biological activities such as antioxidant and anticancer properties. The impact of different solvents of various degree of polarities, on the extraction of antioxidant compounds of Malaysian stingless bee propolis, Trigona apicalis, were studied. Ethanolic extract was found to have the highest yield (28.6 %). The efficiency of solvents for extraction of propolis was found to be in the order of Ethanol > Aqueous> Dichloromethane > Petroleum ether.